2011
DOI: 10.1002/aps.308
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Psychodynamic Psychotherapy and Psychoanalysis in China

Abstract: The history of psychoanalysis in China started already in 1912, followed by a great interest from Chinese intellectuals in the 20s and 30s. Since 1983 psychoanalysts from different Western countries, especially Germany and Norway, teach psychodynamic psychotherapy at Chinese psychiatric institutions. Meanwhile the IPA offers full psychoanalytic training in Beijing and in Shanghai.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…For instance, developed in and improved over the last two approximate decades, videoconference technology Á particularly Skype Á has made distance psychoanalytic supervision increasingly possible, and we have seen accumulating testimony of its international educational benefits (Fishkin, Fishkin, Leli, Katz, & Snyder, 2011;Fonda, 2011;Garcia, 2011;Varvin & Gerlach, 2011;Xu, Qiu, Chen, & Xiao, 2011). As Fishkin et al (2011) have indicated, ''The use of audio-visual protocols appears indispensable for mental health treatment and training in regions where there are no trained psychoanalysts and few are trained in psychoanalytic psychotherapies'' (p. 156).…”
Section: Pressing Needs Impressing Possibilities In Psychoanalytic Smentioning
confidence: 97%
“…For instance, developed in and improved over the last two approximate decades, videoconference technology Á particularly Skype Á has made distance psychoanalytic supervision increasingly possible, and we have seen accumulating testimony of its international educational benefits (Fishkin, Fishkin, Leli, Katz, & Snyder, 2011;Fonda, 2011;Garcia, 2011;Varvin & Gerlach, 2011;Xu, Qiu, Chen, & Xiao, 2011). As Fishkin et al (2011) have indicated, ''The use of audio-visual protocols appears indispensable for mental health treatment and training in regions where there are no trained psychoanalysts and few are trained in psychoanalytic psychotherapies'' (p. 156).…”
Section: Pressing Needs Impressing Possibilities In Psychoanalytic Smentioning
confidence: 97%
“…Leading intellectuals used and discussed psychoanalytic concepts in their work (Zhang 2003), and some of Freud's works were translated into Chinese (Zhang 1992). It was during the thirties that China had its first psychoanalyst, Dr. Bingham Dai, a psychiatrist of Chinese origin who received his training from Harry Stack Sullivan in New York and from Leon Saul in Chicago before returning to China to work at the Peking Union Medical College from 1935 to 1939 (Blowers 2003;Varvin and Gerlach 2011). Psychoanalysis was becoming popular in China, likely more as an instrument for pointing out the weaknesses of society than as a therapy.…”
Section: P S Yc H Oa N a Ly S I S I N T H E C H I N E S E C O N T E X Tmentioning
confidence: 98%
“…Thus, psychoanalysis in China has been received by a population of mental health professionals very different from that in Hong Kong (Varvin and Gerlach 2011;Chang et al 2005;Yang 2011;Xu et al 2011;Yiling, 2013). In the last twenty years, the German-Chinese Academy for Psychotherapy, the Sino-Norway Continuous Training program for Psychodynamic Psychotherapy, and the China American Psychoanalytic Association have mainly been training Chinese psychiatrists and psychologists (mainly from hospitals and universities) in cities like Shanghai, Beijing, Guangzhou, Kunming, Wuhan, and Chengdu.…”
Section: Different Mental Health Professionals' Reception Of Psychoanmentioning
confidence: 98%
“…Specific descriptions of the development of training programs have been contributed by many authors. See Xu Yong (); Varvin and Gerlach () on the Sino‐German and Sino‐Norwegian programs; Fishkin and Fishkin () on the China‐America Psychoanalytic Alliance (CAPA) experience, which introduces analytic therapy from an American point of view; Gerlach () on the development of training in group psychotherapy; and Gullestad () on a model of supervision and teaching in China.…”
Section: Clinical Applications Of Psychoanalysismentioning
confidence: 99%